2014
DOI: 10.4049/jimmunol.1302091
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 Is Expressed by Activated Mouse NK Cells and Inhibits NK Cell IFN-γ Production in Response to Mature Dendritic Cells

Abstract: NK cells express an array of activating and inhibitory receptors that determine NK cell responses upon triggering by cognate ligands. Although activating NK cell receptors recognize mainly ligands expressed by stressed, virus-infected, or transformed cells, most inhibitory receptors engage MHC class I, preventing NK cell activation in response to healthy cells. In this study, we provide insight into the regulation and function of additional receptors involved in mouse NK cell responses: CTLA-4 and CD28. CTLA-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(124 citation statements)
references
References 58 publications
4
118
0
2
Order By: Relevance
“…CTLA-4 expression is induced on CD4 þ and CD8 þ T cells following activation and is constitutively expressed on Tregs (48). A recent study demonstrated that CTLA-4 is also expressed on NK cells upon activation and inhibits their production of IFNg (25). Together, these findings support the potential synergy between DAC and anti-CTLA-4.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…CTLA-4 expression is induced on CD4 þ and CD8 þ T cells following activation and is constitutively expressed on Tregs (48). A recent study demonstrated that CTLA-4 is also expressed on NK cells upon activation and inhibits their production of IFNg (25). Together, these findings support the potential synergy between DAC and anti-CTLA-4.…”
Section: Discussionsupporting
confidence: 72%
“…6K and L), suggesting that NK cells directly execute cell killing in the context of the increased proinflammatory microenvironment. Notably, CTLA-4 was recently shown to be expressed on NK cells upon their activation and to inhibit their production of IFNg (25). Consistently, we observed that CTLA-4 blockade promotes IFNg production by NK cells.…”
Section: Dac Treatment Increases the Number Of Intratumoral T Cells Asupporting
confidence: 76%
“…falciparum malaria, high numbers of CD4 + T cells expressed CTLA4 and PD1 and mostly coexpressed both receptors. Although both, CTLA4 and PD1, are rapidly upregulated after T cell receptor-mediated activation, their expression can also be upregulated by alternative cytokine-based mechanisms [34, 35]. While clearly the vast majority of P .…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that under some circumstances activated NK cells can express programmed cell death protein 1 (PD1; also known as PDCD1) 98,99 and cytotoxic T lymphocyteassociated antigen 4 (CTLA4) 100 , which are the target molecules of several US Food and Drug Administration (FDA)-approved cancer immunotherapy drugs (ipilimumab against CTLA4 and nivolumab and pembrolizumab against PD1) that restore T cell activation. A promising study showed that, in patients with multiple myeloma, NK cells express PD1 and that a PD1 antibody (CT-011) could restore NK cell-mediated antitumour activity 101 .…”
Section: Checkpoint Blockade Of Nk Cellsmentioning
confidence: 99%